The Position of the Pancasila Ideology in the State Administration System: A Study of Philosophy (Law Research Review Quarterly, 2016)
State ideology Pancasila is the direction of national and state life so that it is manifested in a life that upholds Godhead, values ​​of Humanity, awareness of Unity, Society and upholds the value of Justice. This study reveals two things. First, the Pancasila constitutional system occupies a position as the basis and state ideology that is no longer in question, the Pancasila stipulation as a state ideology is listed in MPR Decree No. 18 of 1998 concerning repeal of MPR Decree No. 2 of 1978 concerning Guidelines for the Implementation and Implementation of Pancasila and the affirmation of Pancasila as the State Foundation. Article 1 of the stipulation of the MPR states that Pancasila as intended in the Preamble to the 1945 Constitution is the State Foundation of the Republic of Indonesia which must be carried out consistently in state life. Pancasila must be used as a paradigm (mindset, source of values ​​and orientation of direction) in legal development, including all efforts to reform it. Pancasila can be used as a unifying means of various groups of people in Indonesia, the concept of Pancasila can be understood as a common platform or a common platform for various political ideologies. Pancasila is an offer that can bridge the growing differences, Pancasila has been able to position itself as a place to return if the Indonesian nation is threatened with division. S